MECHANISMS OF STATE SUPPORT FOR SUSTAINABLE AGRICULTURAL PRACTICES IN THE CONDITIONS OF EUROPEAN INTEGRATION AND GLOBAL ENVIRONMENTAL CHALLENGES - TOMASHUK, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the mechanisms of state support for sustainable agricultural practices in the context of the challenges of global ecological transformation and Ukraine's integration into the European Union. The importance of institutional, financial and regulatory support for stimulating environmentally responsible agricultural production is revealed. Attention is focused on the importance of harmonizing national agricultural policy with the principles of the European Green Deal, in particular through the development of agro-ecological subsidy programs, the introduction of "green" lending mechanisms and support for innovative technologies of sustainable land use. Directions for improving state influence instruments are proposed in order to increase the adaptive capacity of the agricultural sector to climate change, preserve natural resource potential and ensure food security. The main principles of greening agriculture are highlighted. The main requirements of the EU for the green transformation of the agrosphere are investigated. The environmental risks for food security are highlighted. A comparative analysis of mechanisms for supporting sustainable agricultural practices in Ukraine and the EU is carried out. An analysis of current programs and financial instruments in the field of sustainable development of the agricultural sector and overcoming environmental risks is carried out. The economic levers of state support for sustainable development of agriculture are summarized. New mechanisms for improving state support for sustainable agricultural practices in the context of European integration are proposed. It is concluded that the state support system should focus on environmentally friendly instruments, such as «eco-schemes», compensation for agro-ecological services, development of organic production and support for small farmers. The results of the study can be used to develop an effective policy of sustainable agricultural development in the context of European integration processes.
Keywords: sustainable development; agricultural policy; environmental challenges; state support; European integration; agriculture; green transformation; institutional mechanisms